RECEPTION ANALYSIS OF PORNOGRAPHY IN VIDEO GAME PLAYER - Jusuf Ariz Wahyuono; Ardian Indro Yuwono (INJECT (Interdisciplinary Journal of Communication), 2019)
This study aims to understand how teenagers know their meaning of pornographic content in the game Dragon Age and The Witcher and understand how this player reproduces the message received. This research used qualitative research methods with the ethnography method. The research subjects consisted of 2 gamers who have different backgrounds on the condition of owning or frequently playing games with pornographic content. The two subjects selected according to criteria, including those who have been playing video games for a long time, are over 18 years old and have free access to video games. The position of each informant in this study shows that they are in the position of negotiated readers. Although both informants actively received pornographic messages in the game, both informants negotiated the meaning of what was received. Each informant negotiates to mean based on their respective fields of reference.